Chemokines and the Signaling Modules Regulating Integrin Affinity - Montresor, Alessio; Toffali, Lara; Constantin, Gabriela; Laudanna, Carlo (Frontiers in Immunology, 2012)
Integrin-mediated adhesion is a general concept referring to a series of adhesive phenomena including tethering-rolling, affinity, valency and binding stabilization altogether controlling cell avidity (adhesiveness) for the substrate. Arrest chemokines modulate each aspect of integrin activation, although integrin affinity regulation has been recognized as the prominent event in rapid leukocyte arrest induced by chemokines. A variety of inside-out and outside-in signaling mechanisms have been related to the process of integrin-mediated adhesion in different cellular models, but only few of them have been clearly contextualized to rapid integrin affinity modulation by arrest chemokines in primary leukocytes. Complex signaling processes triggered by arrest chemokines and controlling leukocyte integrin activation have been described for ras-related rap and for rho-related small GTPases. We summarize the role of rap and rho small GTPases in the regulation of rapid integrin affinity in primary leukocytes and provide a modular view of these pro-adhesive signaling events. A potential, albeit still speculative, mechanism of rho-mediated regulation of cytoskeletal proteins controlling the last step of integrin activation is also discussed. We also discuss data suggesting a functional integration between the rho- and rap-modules of integrin activation. Finally we examine the universality of signaling mechanisms regulating integrin triggering by arrest chemokines.